A proprietary black cumin oil extract (Nigella sativa) (BlaQmax®) modulates stress-sleep-immunity axis safely: Randomized double-blind placebo-controlled study - Mohan, Muttanahally Eraiah; Thomas, Jestin V.; Mohan, Mohind C.; Das S, Syam; Prabhakaran, Prathibha; Pulikkaparambil Sasidharan, Baby Chakrapani (Frontiers in Nutrition, 2023)
Objective: Stress, sleep and immunity are important interdependent factors which play a critical role in the maintenance of health. It has been established that stress can affect sleep, and the quality and duration of sleep significantly impact immunity. However, single drugs capable of targeting these factors are limited because of the multi-targeted mechanism. The present study investigated the influence of a proprietary formulation of thymoquinone-rich black cumin extract (BCO-5) in modulating stress, sleep and hence immunity. Methods: Following the supplementation of BCO-5/placebo at 200 mg/day, a randomized double-blinded placebo-controlled study was carried out on healthy participants with self-reported non-refreshing sleep issues (n = 72). Validated tools of PSQI and PSS were employed for monitoring sleep and stress, respectively, along with the measurement of cortisol and melatonin. Immunity markers were also analyzed at the end of the study. Results: About 70% of participants reported satisfaction with their sleep pattern by day 7 and 79% by day 14. PSS-14 analysis revealed a significant reduction in stress upon both intra (P < 0.001) and intergroup (P < 0.001) comparisons. The observed reduction in stress among the BCO-5 group, with respect to the placebo, was significant, with an effect size of 1.19 by the end of the study (P < 0.001). A significant improvement in the sleep pattern of participants in the BCO-5 group was evident from both inter and intra-group analysis of the total PSQI scores and its component scores (sleep latency, sleep duration, sleep efficiency, sleep quality and daytime dysfunction) on day 45 and day 90. Hematological/immunological parameters further revealed the plausible immunomodulatory effect of BCO-5. Conclusion: BCO-5 significantly modulated the stress-sleep-immunity axis with no side effects and restored restful sleep.